Hubungan Realisasi Alokasi Dana Kesehatan dan Pemanfaatan Pelayanan Kesehatan Ibu di Indonesia - Nafiah, Izzun (UI Scholars Hub, 2020)
Increasing the utilization of maternal health services is an important target for the Indonesian government to increase the achievement of the SDGs targets. Funds budgeted for the health sector are at least 5% of the APBN and 10% of APBD excluding salaries. This is smaller than countries in the low-income category, while WHO shows that an increase in the allocation of health funds has a positive relationship with the degree of public health. Therefore, this study aims to determine whether there is a relationship between the realization of health fund allocation and the utilization of maternal health services in Indonesia. Data source from the 2017 IDHS and provincial government financial statistics. The dependent variables used were the ANC visits, delivery in the public sector, and PNC within two months after delivery. The main independent variable is the realization of health funds and socio-economic characteristics as control variables. With binary logistic regression analysis, the results of this study indicate that the higher the realization of health funds allocation, the more likely the mother is to use maternal health services at the antenatal care and postnatal care stages but reduces the possibility of utilizing childbirth in the public sector.